Transmagnetic dielectric effect material and preparation method thereof

By forming a magnetic nano-multiphase membrane structure through magnetic dielectric effect materials on the surface of the titanium implant, the problems of insufficient biological activity and reduced corrosion resistance of the titanium implant are solved, and the regulation and osseous integration of macrophage polarization are achieved. Improvement of sex.

CN119455114APending Publication Date: 2025-02-18成都医学院第一附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620741.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing titanium implants have insufficient biological activity in the body, which is difficult to effectively promote bone integration, and their corrosion resistance may lead to degeneration and necrosis of tissue cells.

Method used

Using a magnetic dielectric effect material, Cox-(MgF2) layers with different Co contents are deposited successively on a titanium sheet substrate to form a magnetic nano-multiphase film structure with a magnetic dielectric effect. The material is prepared by multi-source sputtering deposition technology, combined with heat treatment, optimizes the microstructure and magnetic characteristics of the multi-phase film.

Benefits of technology

The formed magnetic nano-multiphase membrane structure has good biosafety and can regulate the polarization of macrophages in the implanted body, promote the osteogenic differentiation of bone marrow mesenchymal stem cells, and improve the integration of titanium implants and bone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455114A_ABST
    Figure CN119455114A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of biomedical materials and bioengineering films, and particularly relates to a cross-magnetic dielectric effect material and a preparation method thereof, specifically, magnetic metal particles cobalt (Co) and dielectric ceramic (MgF2) are used as raw materials, and the cross-magnetic dielectric effect material is prepared on the surface of titanium through a multi-source sputtering deposition technology. The magnetic nano-particle multi-phase film with the TMD effect is prepared from the magnetic metal with high saturation magnetization and the dielectric ceramic with high dielectric constant. The titanium sheet with the TMD effect is co-cultured with mouse embryo osteoblast precursor cells (MC3T3-E1) and human gingival fibroblasts (HGF-1) to find that the TMD effect of the titanium sheet has good biological safety, and on the basis, preparation parameters of the multiphase membrane are optimized, so that the polarization of macrophages is regulated and controlled by proper magnetic field force generated by the TMD effect of the titanium sheet, and the macrophages with the TMD effect can be obtained. Therefore, osteogenic differentiation of bone marrow mesenchymal stem cells is promoted, titanium surface osseointegration is improved, and the method is expected to serve as a new direction for preparing a surface coating for promoting implant osseointegration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials and bioengineering films, and in particular relates to a transmagnetic dielectric effect material and a preparation method thereof. Background Art

[0002] With the increase of dental trauma, tumors and periodontal disease, the incidence of tooth loss has reached 52%, which has a significant impact on the quality of life of patients. Implant dentures have gradually become the first choice for patients with tooth loss, which can effectively meet the chewing and aesthetic needs of patients.

[0003] Although titanium implants are widely used due to their good biocompatibility and mechanical properties, there are still some problems that affect their bone integration. First, pure titanium and titanium alloys have insufficient biological activity and lack the ability to stimulate osteoblasts; second, titanium's corrosion resistance in the body decreases, which may lead to tissue cell degeneration and necrosis. Therefore, it is particularly important to improve the long-term stable integration of titanium implants with bones.

[0004] Currently, researchers have used a variety of surface modification techniques to enhance implant-bone integration. These methods include laser treatment and alkali treatment, aiming to form composite coatings such as titanium dioxide nanotubes and hydroxyapatite coatings to improve the biocompatibility and bone integration of implants. However, these coatings are generally still bioinert and have limited effect on improving bioactivity.

[0005] In order to further improve the biological activity of implants, some scholars have proposed organic surface treatment technologies, which can form bioactive coatings containing cell adhesion molecules or growth factors to promote the adhesion and growth of osteoblasts. However, existing coatings still have deficiencies in bonding strength, durability and comprehensive biological performance.

[0006] In recent years, studies have found that magnetic fields have a positive effect on osteogenesis and can promote the directional migration and osteogenic differentiation of bone marrow mesenchymal stem cells. Macrophages play a key role in bone repair, and magnetic fields can regulate their phenotype and function, thereby promoting bone integration. Therefore, how to form a coating with its own magnetic field, strong binding force and good biocompatibility on the surface of titanium implants to regulate macrophage polarization and promote osteogenesis is a topic that needs to be solved urgently.

[0007] The above information disclosed in the above background technology section is only used to enhance the understanding of the background technology of the technology described in this article. Therefore, the background technology may contain certain information that does not form the prior art known in this country to those skilled in the art. Summary of the invention

[0008] In order to solve the defects of the above-mentioned prior art, the present invention proposes a transmagnetic dielectric effect material and a preparation method thereof.

[0009] The technical solution adopted by the present invention is as follows:

[0010] A transmagnetic dielectric effect material comprises a titanium sheet as a substrate, Cox-(MgF2) layers with different Co contents are sequentially deposited on the titanium sheet substrate at room temperature and an argon pressure environment to form a magnetic nano-multiphase film structure with a transmagnetic effect.

[0011] Another aspect of the present invention provides a method for preparing a magnetic dielectric effect material, comprising the following steps:

[0012] (1) Material selection: substrate, Co target, MgF2 target; the substrate is titanium alloy, and the finished product after cutting, grinding and polishing is a 1 cm diameter disc with a thickness of 2 mm;

[0013] (2) Substrate pretreatment: Use an ultrasonic cleaner and an appropriate solvent (such as ethanol or deionized water) to clean the substrate, and blow dry with nitrogen after cleaning to ensure that there is no moisture and impurities on the surface;

[0014] (3) Deposition rate calibration: Calibrate the Co and MgF2 targets to ensure accurate deposition rates;

[0015] (4) Set experimental conditions:

[0016] Ensure that the temperature of the argon environment is 25-35 degrees and the argon content is ≥95%;

[0017] Adjust the argon pressure in the vacuum chamber to 1-10 mTorr;

[0018] (5) Target power setting:

[0019] The fixed sputtering power of the MgF2 target was set to 110 W;

[0020] The power of the Co target is adjusted as needed to set the Co content in each layer to achieve the desired stoichiometric ratio;

[0021] (6) Layered deposition:

[0022] A titanium sheet substrate was placed on the support of the deposition chamber, and Cox-(MgF2) layers with different Co contents were deposited on the substrate in sequence and rotated at a speed of 10,000 rpm to ensure uniform deposition, forming a magnetic nano-multiphase film structure with a transmagnetic effect.

[0023] In a further embodiment, in step 3, the deposition rate parameters recorded before and after calibration are:

[0024] Before calibration: the deposition rates of Co and MgF2 were both 30 nm / h;

[0025] After calibration: the deposition rate of Co and MgF2 is 40nm / h.

[0026] In a further embodiment, the step 6 specifically includes:

[0027] Perform layered deposition according to the set deposition order:

[0028] First layer: deposit a 100nm thick Co layer;

[0029] Second layer: deposit 80nm thick Co layer;

[0030] The third layer: deposit a 60nm thick Co layer;

[0031] After each layer was deposited, wait 1-5 min between each layer to ensure a good interface between layers, record the deposition time and ensure that the deposition rate was maintained at 40 nm / h.

[0032] In a further embodiment, the magnetic nano-multiphase film structure on the surface of the titanium sheet is characterized:

[0033] Magnetic properties measurement: Use vibrating sample magnetometer to measure the magnetic properties of titanium sheets, especially the magnetic characteristics of multiphase films. This method can provide parameters such as magnetic saturation, residual magnetic induction and coercivity of the sample.

[0034] Microstructure observation: Scanning electron microscopy was used to observe the microstructure of the multiphase membrane, including the thickness, uniformity, and possible defects or discontinuities of the membrane.

[0035] Element distribution analysis: Use an energy spectrum analyzer to analyze the element composition and distribution of the multiphase film surface through surface scanning technology. Surface roughness detection: Use a roughness meter to measure the arithmetic average roughness (Ra) and average roughness (Rz) of the multiphase film surface.

[0036] Contact angle measurement: The contact angle of the multiphase film surface is measured using a contact angle meter to evaluate its wettability.

[0037] Binding force test: By controlling the pressure head to press into the surface of the multiphase membrane, recording the relationship between load and indentation depth, the mechanical properties of the membrane and the ability of the structure to resist deformation due to external forces are analyzed.

[0038] Study on ion release behavior: The cleaned and dried samples were placed in DMEM complete culture medium, and the changes in Co and Mg ion concentrations at different time points (1st day, 4th day, 7th day and 14th day) were monitored. Inductively coupled plasma mass spectrometry was used for analysis to evaluate the release of ions in the multiphase membrane.

[0039] In a further embodiment, heat treatment is performed after the deposition is completed in step 6 to improve the crystallinity and physical properties of the film.

[0040] In a further embodiment, step 6 further includes:

[0041] The titanium sheet with the multiphase film of magnetic-transmissive dielectric effect is packaged and sterilized.

[0042] Another aspect of the present invention provides an application of the magnetically permeable dielectric effect material in implant bone.

[0043] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0044] In general, compared with the prior art, the present invention provides a transmagnetic dielectric effect material and a preparation method thereof. Using magnetic metal particles cobalt (Co) and dielectric ceramics (MgF2) as raw materials, a magnetic metal with high saturation magnetization and a dielectric ceramic with high dielectric constant are prepared on a titanium surface by multi-source sputtering deposition technology to form a magnetic nanoparticle multiphase film with TMD effect. The titanium sheet with the above TMD effect was co-cultured with mouse embryonic osteoblast precursor cells (MC3T3-E1) and human gingival fibroblasts (HGF-1), respectively, and it was found that the TMD effect of the titanium sheet had good biosafety. On this basis, the multiphase film preparation parameters are optimized so that the magnetic field force of the appropriate size generated by the TMD effect of the titanium sheet regulates the polarization of macrophages, thereby promoting the osteogenic differentiation of bone marrow mesenchymal stem cells and improving the bone integration of the titanium surface, which is expected to be a new direction for the preparation of surface coatings that promote the bone integration of implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The present invention will now be described by way of example with reference to the accompanying drawings, in which:

[0046] Figure 1 is a flow chart of the preparation method of the present invention;

[0047] Figure 2 The schematic diagram of the preparation principle of the magnetic dielectric effect material in the present invention;

[0048] Figure 3 This is a diagram showing the results of the microscopic morphology observation of the multiphase membrane surface in the present invention;

[0049] Figure 4 This is a diagram showing the results of the detection and observation of the surface roughness of the multiphase membrane in the present invention;

[0050] Figure 5 The figure shows the contact angle measurement results of the multiphase film surface in the present invention. DETAILED DESCRIPTION

[0051] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The components of the embodiments of the present application usually described and shown in the drawings here can be arranged and designed in various configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.

[0052] This embodiment provides a transmagnetic dielectric effect material, including a titanium sheet as a substrate, and sequentially depositing Cox-(MgF2) layers with different Co contents on the titanium sheet substrate at room temperature and argon pressure environment to form a magnetic nano-multiphase film structure with transmagnetic effect. The preparation principle is as follows: Figure 2 The titanium substrate is rotated at a speed of 10 rpm, and high-energy particles are used to bombard the Co target and MgF2 target, so that the atoms in the target are sputtered out and deposited on the substrate surface to form a thin film.

[0053] Example 1

[0054] A method for preparing a magnetic dielectric effect material, see Figure 1 , including the following steps:

[0055] (1) Material selection: substrate, Co target, MgF2 target; the substrate is titanium alloy, and the finished product after cutting, grinding and polishing is a 1 cm diameter disc with a thickness of 2 mm;

[0056] (2) Substrate pretreatment: Use an ultrasonic cleaner and an appropriate solvent (such as ethanol or deionized water) to clean the substrate, and blow it dry with nitrogen after cleaning to ensure that there is no moisture and impurities on the surface.

[0057] (3) Deposition rate calibration: Calibrate the Co and MgF2 targets to ensure accurate deposition rates;

[0058] The deposition rate parameters recorded before and after calibration are:

[0059] Before calibration: the deposition rates of Co and MgF2 were both 30 nm / h;

[0060] After calibration: the deposition rate of Co and MgF2 is 40nm / h.

[0061] (4) Set experimental conditions:

[0062] Ensure that the temperature of the argon environment is 25-35 degrees and the argon content is ≥95%;

[0063] Adjust the argon pressure in the vacuum chamber to 1-10 mTorr.

[0064] (5) Target power setting:

[0065] The fixed sputtering power of the MgF2 target was set to 150 W;

[0066] The fixed sputtering power of the Co target was set to 110 W, and the content of Co in each layer was set to reach the expected stoichiometric ratio of 16.00%, the stoichiometric ratio of Mg was 20.57%, the stoichiometric ratio of F was 54.86%, and the stoichiometric ratio of Ti was 8.57%.

[0067] (6) Layered deposition:

[0068] A titanium substrate is placed on the bracket of the deposition chamber, and Cox-(MgF2) layers with different Co contents are deposited on the substrate in sequence, and rotated at a speed of 10,000 rpm to ensure uniform deposition. By controlling the sputtering target time at 90 minutes, a film with a thickness of 615 nm can be prepared, and after adding Co metal target, a Ti-Cox / MgF2-1 magnetic nano-multiphase film structure with a transmagnetic dielectric effect is formed; after deposition, heat treatment is performed to improve the crystallinity and physical properties of the film.

[0069] Each layer is deposited in a layered manner according to the set deposition order:

[0070] First layer: deposit a 100nm thick Co layer;

[0071] Second layer: deposit 80nm thick Co layer;

[0072] The third layer: deposit a 60nm thick Co layer;

[0073] After each layer was deposited, wait 1-5 min between each layer to ensure a good interface between layers, record the deposition time and ensure that the deposition rate was maintained at 40 nm / h.

[0074] (7) Packaging and sterilization:

[0075] The titanium sheet with the multiphase film of magnetic-transmissive dielectric effect is packaged and sterilized.

[0076] Example 2

[0077] A method for preparing a transmagnetic dielectric effect material comprises the following steps:

[0078] (1) Material selection: substrate, Co target, MgF2 target; the substrate is titanium alloy, and the finished product after cutting, grinding and polishing is a 1 cm diameter disc with a thickness of 2 mm;

[0079] (2) Substrate pretreatment: Use an ultrasonic cleaner and an appropriate solvent (such as ethanol or deionized water) to clean the substrate, and blow it dry with nitrogen after cleaning to ensure that there is no moisture and impurities on the surface.

[0080] (3) Deposition rate calibration: Calibrate the Co and MgF2 targets to ensure accurate deposition rates;

[0081] The deposition rate parameters recorded before and after calibration are:

[0082] Before calibration: the deposition rates of Co and MgF2 were both 30 nm / h;

[0083] After calibration: the deposition rate of Co and MgF2 is 40nm / h.

[0084] (4) Set experimental conditions:

[0085] Ensure that the temperature of the argon environment is 25-35 degrees and the argon content is ≥95%;

[0086] Adjust the argon pressure in the vacuum chamber to 1-10 mTorr.

[0087] (5) Target power setting:

[0088] The fixed sputtering power of the MgF2 target was set to 150 W;

[0089] The fixed sputtering power of the Co target was set to 110 W, and the content of Co in each layer was set to reach the expected stoichiometric ratio of 15.46%, the stoichiometric ratio of Mg was 14.43%, the stoichiometric ratio of F was 38.15%, and the stoichiometric ratio of Ti was 31.96%.

[0090] (6) Layered deposition:

[0091] A titanium substrate is placed on the bracket of the deposition chamber, and Cox-(MgF2) layers with different Co contents are deposited on the substrate in sequence, and rotated at a speed of 10,000 rpm to ensure uniform deposition. By controlling the sputtering target time at 45 minutes, a thin film with a thickness of 300 nm can be prepared, and after adding Co metal target, a Ti-Cox / MgF2-2 magnetic nano-multiphase film structure with a transmagnetic dielectric effect is formed; after deposition, heat treatment is performed to improve the crystallinity and physical properties of the film.

[0092] Each layer is deposited in a layered manner according to the set deposition order:

[0093] First layer: deposit a 100nm thick Co layer;

[0094] Second layer: deposit 80nm thick Co layer;

[0095] The third layer: deposit a 60nm thick Co layer;

[0096] After each layer was deposited, wait 1-5 min between each layer to ensure a good interface between layers, record the deposition time and ensure that the deposition rate was maintained at 40 nm / h.

[0097] (7) Packaging and sterilization:

[0098] The titanium sheet with the multiphase film of magnetic-transmissive dielectric effect is packaged and sterilized.

[0099] Comparative Example 1

[0100] Different from the embodiments 1 and 2, in this comparative example, only the MgF2 target is sputtered and deposited, the fixed sputtering power of the MgF2 target is set to 150W, the stoichiometric ratio of Mg is 9.66%, the stoichiometric ratio of F is 8.15%, the stoichiometric ratio of Ti is 82.19%, and the sputtering target time is controlled at 55min, and a Ti-MgF2-1 magnetic nano-multiphase film structure with a transmagnetic dielectric effect and a thickness of 46nm can be prepared.

[0101] Comparative Example 2

[0102] Different from the embodiments 1 and 2, in this comparative example, only the MgF2 target is sputtered and deposited, the fixed sputtering power of the MgF2 target is set to 150W, the stoichiometric ratio of Mg is 16.47%, the stoichiometric ratio of F is 22.39%, the stoichiometric ratio of Ti is 61.14%, and the sputtering target time is controlled at 120min, and a Ti-MgF2-2 magnetic nano-multiphase film structure with a transmagnetic dielectric effect and a thickness of 150nm can be prepared.

[0103] Comparative Example 3

[0104] Different from the embodiments 1 and 2, in this comparative example, only the MgF2 target is sputtered and deposited, the fixed sputtering power of the MgF2 target is set to 150W, the stoichiometric ratio of Mg is 23.13%, the stoichiometric ratio of F is 33.59%, and the stoichiometric ratio of Ti is 43.28%. The sputtering target time is controlled at 240min, and a Ti-MgF2-3 magnetic nano-multiphase film structure with a transmagnetic dielectric effect and a thickness of 260nm can be prepared.

[0105] The contents of the components of the surface titanium film in the above-mentioned Examples 1, 2 and Comparative Examples 1-3 are as follows in Table 1:

[0106]

[0107] The titanium film preparation parameters in the above-mentioned Examples 1, 2 and Comparative Examples 1-3 are shown in Table 2 below:

[0108] The magnetic nano-multiphase film structure on the surface of the titanium sheet in Examples 1 and 2 and Comparative Examples 1-3 was characterized:

[0109] Magnetic properties measurement: Use vibrating sample magnetometer to measure the magnetic properties of titanium sheets, especially the magnetic characteristics of multiphase films. This method can provide parameters such as magnetic saturation, residual magnetic induction and coercivity of the sample.

[0110] Microscopic morphology observation: Scanning electron microscopy is used to observe the microscopic morphology of the multiphase membrane, including the thickness, uniformity, and possible defects or discontinuities of the membrane. The observation results will be displayed in images (such as Figure 3 ) is presented.

[0111] Element distribution analysis: Use an energy spectrum analyzer to analyze the element composition and distribution of the multiphase film surface through surface scanning technology. This helps to quantify the proportion and distribution characteristics of elements such as Co, Mg, and F in the film.

[0112] Surface roughness test: Use a roughness meter to measure the arithmetic mean roughness (Ra) and average roughness (Rz) of the multiphase membrane surface. Roughness data can reflect the surface characteristics of the membrane and evaluate the impact of the TMD effect. The test results are as follows: Figure 4 shown.

[0113] Contact angle measurement: Use a contact angle meter to measure the contact angle of the multiphase membrane surface to evaluate its wettability. Data analysis will be completed using FAMAS software to help understand surface energy and surface tension. Test results such as Figure 5 shown.

[0114] Binding force test: By controlling the pressure head to press into the surface of the multiphase membrane, recording the relationship between load and indentation depth, the mechanical properties of the membrane and the ability of the structure to resist deformation due to external forces are analyzed.

[0115] Study on ion release behavior: The cleaned and dried samples were placed in DMEM complete culture medium, and the changes in Co and Mg ion concentrations at different time points (1st day, 4th day, 7th day and 14th day) were monitored. Inductively coupled plasma mass spectrometry was used for analysis to evaluate the release of ions in the multiphase membrane.

[0116] On the other hand, the present invention also provides an application of the magnetically permeable dielectric effect material in implant bone, which can form a multiphase film on the surface of a titanium sheet, and by optimizing the preparation parameters, the microstructure and magnetic characteristics of the film are regulated, thereby generating an appropriate magnetic field force when implanted in the body.

[0117] The TMD effect on the titanium sheet can generate a certain magnetic field force, which has a regulatory effect on the polarization of macrophages. The polarization state of macrophages is crucial to the bone regeneration and repair process. By adjusting the size and direction of the magnetic field, the function of macrophages can be affected, causing them to shift to a polarization state that is conducive to bone healing.

[0118] Polarization of macrophages under optimized magnetic fields can promote the differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts. This process is important for improving bone healing and integration, as osteoblasts are responsible for the formation and regeneration of bone tissue.

[0119] Through the above mechanism, the titanium sheet surface optimized by the transmagnetic dielectric effect material can not only improve the osteogenic ability of bone marrow mesenchymal stem cells, but also enhance the bone integration of the titanium surface. This means that the implanted titanium implant can integrate with the surrounding bone tissue faster and more firmly, thereby improving the implantation success rate and long-term stability.

[0120] The present invention provides a new direction for the preparation of implant surface coatings. By studying and applying transmagnetic dielectric effect materials, a titanium sheet with functionalized surface can be developed to promote the interaction between implants and bone tissue, opening up new possibilities for the clinical application of implants.

[0121] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A transmagnetic dielectric effect material, characterized in that: The method comprises taking a titanium sheet as a substrate and sequentially depositing Cox-(MgF2) layers with different Co contents on the titanium sheet substrate at room temperature and under an argon pressure environment to form a magnetic nano-multiphase film structure with a transmagnetic effect.

2. A method for preparing a transmagnetic dielectric effect material, characterized in that: The steps include: (1) Material selection: substrate, Co target, MgF2 target; the substrate is titanium alloy, and the finished product after cutting, grinding and polishing is a 1 cm diameter disc with a thickness of 2 mm; (2) Substrate pretreatment: Use an ultrasonic cleaner and an appropriate solvent (such as ethanol or deionized water) to clean the substrate, and blow dry with nitrogen after cleaning to ensure that there is no moisture and impurities on the surface; (3) Deposition rate calibration: Calibrate the Co and MgF2 targets to ensure accurate deposition rates; (4) Set experimental conditions: Ensure that the temperature of the argon environment is 25-35 degrees and the argon content is ≥95%; Adjust the argon pressure in the vacuum chamber to 1-10 mTorr; (5) Target power setting: The fixed sputtering power of the MgF2 target was set to 110 W; The power of the Co target is adjusted as needed to set the Co content in each layer to achieve the desired stoichiometric ratio; (6) Layered deposition: A titanium sheet substrate was placed on the support of the deposition chamber, and Cox-(MgF2) layers with different Co contents were deposited on the substrate in sequence and rotated at a speed of 10,000 rpm to ensure uniform deposition, forming a magnetic nano-multiphase film structure with a transmagnetic effect.

3. The method for preparing a transmagnetic dielectric effect material according to claim 2, characterized in that: In step 3, the deposition rate parameters recorded before and after calibration are: Before calibration: the deposition rates of Co and MgF2 were both 30 nm / h; After calibration: the deposition rate of Co and MgF2 is 40nm / h.

4. The method for preparing a transmagnetic dielectric effect material according to claim 2, characterized in that: The step 6 specifically includes: Perform layered deposition according to the set deposition order: First layer: deposit a 100nm thick Co layer; Second layer: deposit 80nm thick Co layer; The third layer: deposit a 60nm thick Co layer; After each layer was deposited, wait 1-5 min between each layer to ensure a good interface between layers, record the deposition time and ensure that the deposition rate was maintained at 40 nm / h.

5. The method for preparing a transmagnetic dielectric effect material according to claim 2, characterized in that: It also includes the characterization of the magnetic nano-multiphase film structure on the surface of the titanium sheet: Magnetic properties measurement: Use vibrating sample magnetometer to measure the magnetic properties of titanium sheets, especially the magnetic characteristics of multiphase films; Microscopic morphology observation: Use scanning electron microscopy to observe the microscopic morphology of the multiphase membrane, including the thickness, uniformity, and possible defects or discontinuities of the membrane; Element distribution analysis: Use energy spectrum analyzer and surface scanning technology to analyze the element composition and distribution on the surface of multiphase membranes; Surface roughness detection: Use a roughness meter to measure the arithmetic mean roughness and average roughness of the multiphase film surface; Contact angle measurement: Use a contact angle meter to measure the contact angle of the multiphase membrane surface to evaluate its wettability. Adhesion test: By controlling the pressure head to press into the multiphase membrane surface, record the relationship between load and indentation depth, and analyze the membrane's mechanical properties and the ability of the structure to resist external force deformation; Study on ion release behavior: The cleaned and dried samples were placed in DMEM complete culture medium, and the changes in Co and Mg ion concentrations were monitored on the 1st, 4th, 7th and 14th days. Inductively coupled plasma mass spectrometry was used for analysis to evaluate the release of ions in the multiphase membrane.

6. The method for preparing a transmagnetic dielectric effect material according to claim 2, characterized in that: After deposition, heat treatment is performed to improve the crystallinity and physical properties of the film.

7. The method for preparing a transmagnetic dielectric effect material according to claim 2, characterized in that: The step 6 also includes: The titanium sheet with the multiphase film of magnetic-transmissive dielectric effect is packaged and sterilized.

8. An application of the magnetically permeable dielectric effect material according to claim 1 in implant bone.